Dirt on photovoltaic modules and efficient energy generation in the Brazilian semiarid - Tiago L. S. de Souza; Regina L. F. A. Lima; Claudemiro de Lima Júnior (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT A photovoltaic electrical energy system is one of the least aggressive ways to affect the environment. Factors such as dirt influence the efficiency of these systems and can have a considerable impact in low rainfall regions, such as the Brazilian semiarid. In this respect, the aim of the present study was to analyze the effect of dirt on the efficiency of electricity generation in photovoltaic modules installed in the Brazilian semiarid. To that end, the output power of a periodically cleaned module was compared with a naturally dirty module; in addition, the percentage output power, dirt deposition density and relationship between these variables were estimated. The study was carried out at the University of Pernambuco, in the city of Petrolina, PE, Brazil, during dry and rainy periods. Data were collected via a data acquisition system and dirt using glass slides. The results indicate that more than 15 days without rain significantly reduces the efficiency of photovoltaic modules installed in semiarid areas, reaching an 18.72% decrease in output power after 70 days.